Ventral-Onlay Buccal Mucosal Graft Urethroplasty of a Perineal Fistula in a 26-Year-Old Patient With 46 XX Male Syndrome: A Case Report. Issue 2 (April 2023) - Hosseini, Jalil; Zamani Hajiabadi, Arshia; Mirjalili, Ali Mohammad
Substitution urethroplasty with either a flap or graft is the gold standard for treating long segment urethral strictures. In 1992, Burger and colleagues rediscovered and popularized buccal mucosal graft (BMG). After that El-Kassaby and colleagues, in 1993, used BMG to repair anterior urethral stricture. De la Chapelle syndrome or 46 XX male syndrome is a rare genetic disorder found in 1 in 20, 000–25, 000 men. This condition described as a presentation of male phenotype along a 46 xx karyotype. In this case report, we report a reconstructive surgery of a 46 XX male syndrome with ambiguous genitalia who presented with the chief complaint of bulbar urethral fistula opened in the perineal space. In this case, we used a buccal mucous graft with the ventral-onlay urethroplasty technique for reconstructing the failed bulbar urethra and closure of the fistula.